Respostas
respondido por:
0
3a + b = 1
-5a + b = 2 (multiplica por -1) e soma com a eq. 1
=======
3a + b = 1
5a - b = -2
----------------
8a = -1
a = -1/8. achamos b
=========
3a + b = 1
-3/8 + b = 1
b = 1 + 3/8
b = 11/8
=========
queremos a + b
-1/8 + 11/8 =
10/8 simplificando
5/4
-5a + b = 2 (multiplica por -1) e soma com a eq. 1
=======
3a + b = 1
5a - b = -2
----------------
8a = -1
a = -1/8. achamos b
=========
3a + b = 1
-3/8 + b = 1
b = 1 + 3/8
b = 11/8
=========
queremos a + b
-1/8 + 11/8 =
10/8 simplificando
5/4
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás